Long-term outcome after combined or sequential liver and kidney transplantation in children with infantile and juvenile primary hyperoxaluria type 1 - Loos, Sebastian; Kemper, Markus J.; Schmaeschke, Kaja; Herden, Uta; Fischer, Lutz; Hoppe, Bernd; Levart, Tanja Kersnik; Grabhorn, Enke; Schild, Raphael; Oh, Jun; Brinkert, Florian (Frontiers in Pediatrics, 2023)
Introduction Combined or sequential liver and kidney transplantation (CLKT/SLKT) restores kidney function and corrects the underlying metabolic defect in children with end-stage kidney disease in primary hyperoxaluria type 1 (PH1). However, data on long-term outcome, especially in children with infantile PH1, are rare. Methods All pediatric PH1-patients who underwent CLKT/SLKT at our center were analyzed retrospectively. Results Eighteen patients (infantile PH1 n = 10, juvenile PH1 n = 8) underwent transplantation (CLKT n = 17, SLKT n = 1) at a median age of 5.4 years (1.5–11.8). Patient survival was 94% after a median follow-up of 9.2 years (6.4–11.0). Liver and kidney survival-rates after 1, 10, and 15 years were 90%, 85%, 85%, and 90%, 75%, 75%, respectively. Age at transplantation was significantly lower in infantile than juvenile PH1 (1.6 years (1.4–2.4) vs. 12.8 years (8.4–14.1), P = 0.003). Median follow-up was 11.0 years (6.8–11.6) in patients with infantile PH1 vs. 6.9 years (5.7–9.9) in juvenile PH1 (P = 0.15). At latest follow-up kidney and/or liver graft loss and/or death showed a tendency to a higher rate in patients with infantile vs. juvenile PH1 (3/10 vs. 1/8, P = 0.59). Discussion In conclusion, the overall patient survival and long-term transplant outcome of patients after CLKT/SLKT for PH1 is encouraging. However, results in infantile PH1 tended to be less optimal than in patients with juvenile PH1.